2006
DOI: 10.1590/s0103-50532006000700026
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and photocatalytic properties of novel M2BiNbO7 (M = In and Ga)

Abstract: Os óxidos M 2 BiNbO 7 (M = In e Ga) foram sintetizados através de reações no estado sólido, e suas propriedades estruturais e fotocatalíticas, investigadas. Os resultados indicaram que estes compostos cristalizam na estrutura do tipo pirocloro, no sistema cúbico, grupo espacial Fd-3m. Os valores estimados dos "band gaps" dos óxidos In 2 BiNbO 7 e Ga 2 BiNbO 7 são 2,52(5) e 2,57(8) eV, respectivamente. A reação fotocatalítica da decomposição de água pura foi estudada na presença dos fotocatalisadores M 2 BiNbO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…159 A series of A 3 MO 3 (A = Bi, Al, Ga and In, M = Nb and Ta) has been reported. 160,161 5.1.3 Group 6 and other d 0 elements [147][148][149][150][151] . PbWO 4 with scheelite structure and RbWMO 6 (M = Nb and Ta) with pyrochlore structure are active.…”
Section: Group 4 Elementsmentioning
confidence: 99%
“…159 A series of A 3 MO 3 (A = Bi, Al, Ga and In, M = Nb and Ta) has been reported. 160,161 5.1.3 Group 6 and other d 0 elements [147][148][149][150][151] . PbWO 4 with scheelite structure and RbWMO 6 (M = Nb and Ta) with pyrochlore structure are active.…”
Section: Group 4 Elementsmentioning
confidence: 99%
“…The characteristic of the transition depends upon the value of n : it is 1/2 for direct and 2 for indirect transition, respectively. The method to evaluate the value of n is given somewhere else . By following this method, it was found that the MM–10 and Fe-modified MM–10 show direct allowed transitions.…”
Section: Resultsmentioning
confidence: 99%
“…The method to evaluate the value of n is given somewhere else. 39 By following this method, it was found that the MM−10 and Fe-modified MM−10 show direct allowed transitions. The band gap energies of the Fe@MM−10 NC samples can be estimated from the plots of (αhν) 2 versus photon energy (hν).…”
Section: α υ υmentioning
confidence: 99%
“…Single-phase quaternary oxide materials have been recently studied with the aim to develop novel photocatalysts showing high activity in the visible light region. Luan and coworkers [416][417][418][419][420][421][422][423][424][425] synthesized various series of these compounds utilizing binary oxides as the starting materials. In particular, these series contained Ta (Bi 2 MTaO 7 (M = Ga, In, La, Y)) [416][417][418], Nb (M 2 BiNbO 7 (M = In and Ga)) [419], V (Bi 2 MVO 7 (M = Ga, Fe, Al, Sb)) [420][421][422][423] or Sb (Y 2 MSbO 7 (M = Fe, In)) [424,425].…”
Section: Quaternary Oxidesmentioning
confidence: 99%